Accounting for the C/city: analyzing Kisumu's fiscal configurations - Cirolia, Liza Rose (Department of Environmental and Geographical Science, 2019)
Urban public finance is a hidden force shaping cities and their development. This thesis draws attention to the powerful insights which can be gained from studying cities through a fiscal lens. It argues for an interdisciplinary and relational approach which infuses the fiscal study of cities with political and social interpretations of urban dynamics. Accounting for the city through two very different registers, this thesis draws from urban public finance and from critical scholarship on urban infrastructure. The conventional urban public finance literature is largely technical, produced by urban policy and fiscal experts. In contrast, social and political theorization on urban infrastructure provides a critical reading of the technicist approach and contributes to the refinement of key theoretical concepts within urban studies. There are many incommensurabilities between these two scholarly registers. They have different framings of politics, technical knowledge, and the priorities for change. However, there are several shared interests. They are both concerned with urban institutions, urban places, and the necessity for change. These shared interests provide the foundation for a revised approach to the fiscal study of cities. This synthetic approach is spelled out in a series of conceptual and methodological propositions. The first proposition is the device of the C/city, which distinguishes between an urban settlement (the small ccity) and its governing authorities (the big-C City). The C/city device foregrounds the importance of the city, the City, and the fiscal relationships which operate at the intersections between them. The second proposition frames urban public finance not just as a means of financing urban infrastructure but as an infrastructure itself. Drawing from the infrastructure scholarship, the concept of 'configurations’ is deployed creatively to trace fiscal histories, instruments, and relationships. The third proposition is the importance of grounding inquiry in particular places. To address this, the case study method is used. The case method allows for the use of a variety of types of data and analytical tools, grounded in contextualized experiences. The fourth proposition presents Kisumu, a secondary city in Kenya, as an exemplary case for exploring fiscal C/city configurations. Kisumu provides a useful case for wider generalization precisely because it is an ordinary (African) city. Not only is Kisumu on the margins of Western theorization, its unsensational nature also excludes it from dominant discourses on African cities. However, historically, administratively, and politically, Kisumu has many parallels with smaller urban centers in British East Africa and beyond. It provides a fascinating and widely relevant case of the differentiated nature of fiscal decentralization processes and dynamics. There is much which can be learned from Kisumu and its fiscal story. The bulk of this thesis is dedicated to unpacking the Kisumu case. First, there is a focus on the City. This includes tracing the historical development of Kisumu’s urban institutions and unpacking the ways in which the contemporary City shapes and is shaped by public finance. This is followed by a deeper exploration of particular city infrastructures and their fiscal configurations. The fiscal configurations related to property rates, the corporatized water utility company, and transport finance are traced and exposed. The Kisumu case provides a series of valuable insights. First, it demonstrates the potential and limitations of conventional fiscal analysis. The limitations posed by accounting are particularly important in the context of Kisumu, where the C/city has many misalignments. Second, it makes the case for reading public finance as an urban infrastructure. The process of tracing fiscal configurations illuminates the social, political, material and technical dimensions of public finance. Third, it draws attention to the de facto challenges and complexities related to decentralization (and in fact, the unique recentralization which Kenya has undergone). This includes how the sub-national urban state is constructed and deconstructed, over time and in complex ways. Fourth, it foregrounds the fiscal functionaries whose practices shape the everyday operations of the public finance system. These actors shape fiscal configurations. However, they are often hidden in conventional fiscal analyses. Fifth, it reads the practices of fiscal functionaries as a micro-politics of the state. The heterogeneity of the state and multidimensional nature of power are foregrounded. Finally, the case highlights the challenge of urban infrastructure finance in the context of a post-networked city. It shows the necessity of moving beyond common academic and policy tropes related to infrastructure and services. Collectively, these insights provide a compelling case for urban studies to more deeply engage with the fiscal C/city, in Africa and beyond.